2019
DOI: 10.1097/ijg.0000000000001180
|View full text |Cite
|
Sign up to set email alerts
|

Central Corneal Thickness Variances Among Different Asian Ethnicities in Glaucoma and Nonglaucoma Patients

Abstract: Objective: To compare the central corneal thickness (CCT) between different ethnicities and particularly Asian subethnic groups that may contribute to the different glaucoma diagnoses using the optical low-coherence reflectometry technique. Methods: A retrospective study of 6 years including 1512 eyes of 929 patients of the Beckman vision center, University of California, San Francisco from 2011 to 2017 had their biometric parameters, including CCT, mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 49 publications
1
18
1
Order By: Relevance
“…For this study, our GERA sample consisted of 18,129 individuals from four ethnic groups (79.9% non-Hispanic white, 7.5% Hispanic/Latino, 8.4% East Asian, and 4.2% African American) with a measured CCT (Table 1). In our GERA sample, African Americans had thinner CCTs on average than other groups, consistent with previous reports [5][6][7] .…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…For this study, our GERA sample consisted of 18,129 individuals from four ethnic groups (79.9% non-Hispanic white, 7.5% Hispanic/Latino, 8.4% East Asian, and 4.2% African American) with a measured CCT (Table 1). In our GERA sample, African Americans had thinner CCTs on average than other groups, consistent with previous reports [5][6][7] .…”
Section: Resultssupporting
confidence: 92%
“…Reduced CCT is a feature of keratoconus 1 , and, by some accounts, is associated with an increased risk of primary open-angle glaucoma (POAG) [2][3][4] . Epidemiological observational studies have implicated demographic and clinical risk factors that influence CCT, including, sex, glaucoma diagnosis, and ethnicity [5][6][7][8] . Individuals of African ancestry have thinner CCT but also increased POAG risk, and have worse visual field damage and disease progression compared to other populations [5][6][7]9,10 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 19 It should be noted that pachymetry values can vary with gender and age, and differ between ethnic groups as well as measurement techniques. 20 , 21 Therefore, to apply this extended criteria in different clinical settings should be considered with caution. Although, all patients in our cohort had pre-operative CCT values that complied with the guideline, we found that 9 (9.57%) patients eventually developed CEF within the 10 years of follow-up period, corresponding to the incidence rate of 26 per 1000 person years.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported to be thinner in elders and African-Americans than in whites [6,7]. Some studies showed that men had thicker corneas [8,9]. So, this study aimed to give reference values of the central corneal thickness with different refractive errors for the adult Egyptian population.…”
Section: Introductionmentioning
confidence: 98%